Identification of Tourism-Based MSME Marketing Management Strategies - Hermawan, Romy; Supriono, Supriono; Rizaldi, Rasyid Akbar; Sudarmiatin, Sudarmiatin (Journal of Indonesia Marketing Association (IMA), 2024)
Sugihwaras Village is a village located in Ngancar District, Kediri Regency. The Sugihwaras Village area includes plantation areas, forestry areas and the Mount Kelud Tourism Area, which means that some economic activities take place in the agricultural and tourism sectors. A well-known agricultural commodity is pineapple with a typical mainstay product, namely "kelud “Madu” pineapple". The superiority of commodities and the implementation of tourism activities in the Mount Kelud Tourism Area has created new job opportunities, namely Kelud “Madu” Pineapple Traders. In practice, Kelud “Madu” pineapple traders are part of Micro, Small and Medium Enterprises (MSMEs) and as an aspect of Tourism Amenities to support tourism activities in the Mount Kelud Tourism Area. The Kediri Regency Government also supports the potential of “Madu” pineapple in Sugihwaras Village by holding a Pineapple Festival to develop and commercialize the potential of kelud “Madu” pineapple. However, the government's objectives are still not in line with the conditions of MSMEs selling kelud “Madu” pineapples. Therefore, this research seeks to examine marketing management by Kelud “Madu” pineapple traders as supporters of the Mount Kelud Tourism Area. This research uses a qualitative method with an exploratory descriptive approach. Data collection techniques use interviews, observation and documentation. Data analysis consists of data collection, data condensation, data presentation, and drawing conclusions. The research results show that marketing by kelud “Madu” pineapple traders is considered to be quite good in terms of potential, personal, operational, relationship and interaction management. The obstacles encountered by kelud “Madu” pineapple traders are related to the provision of facilities, high purchasing prices, and declining sales. Efforts made by the government include organizing festivals and community training, but there is a need for capital assistance for traders.